2010
DOI: 10.1111/j.1462-2920.2009.02065.x
|View full text |Cite
|
Sign up to set email alerts
|

Deep sequencing reveals exceptional diversity and modes of transmission for bacterial sponge symbionts

Abstract: Marine sponges contain complex bacterial communities of considerable ecological and biotechnological importance, with many of these organisms postulated to be specific to sponge hosts. Testing this hypothesis in light of the recent discovery of the rare microbial biosphere, we investigated three Australian sponges by massively parallel 16S rRNA gene tag pyrosequencing. Here we show bacterial diversity that is unparalleled in an invertebrate host, with more than 250 000 sponge-derived sequence tags being assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

34
436
7
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(493 citation statements)
references
References 59 publications
34
436
7
3
Order By: Relevance
“…Although present in all samples, the Cyanobacteria were particularly abundant (8-24% relative abundance) in Heterostegina depressa and in one Marginopora vertebralis sample (17% relative abundance). The composition of microbial communities associated with the sponge Rhopaloeides odorabile was different to those associated with other invertebrates, although this community pattern is consistent with a previous investigation (Webster et al, 2010).…”
supporting
confidence: 78%
“…Although present in all samples, the Cyanobacteria were particularly abundant (8-24% relative abundance) in Heterostegina depressa and in one Marginopora vertebralis sample (17% relative abundance). The composition of microbial communities associated with the sponge Rhopaloeides odorabile was different to those associated with other invertebrates, although this community pattern is consistent with a previous investigation (Webster et al, 2010).…”
supporting
confidence: 78%
“…Proteobacteria (the a-subdivision), Cyanobacteria and Euryarchaeota were the most dominant groups in all our seawater samples (Figures 5 and 6). Although these phyla also dominated other planktonic systems (Morris et al, 2002;Giovannoni and Stingl, 2005), the microbial diversity in our samples was low in comparison with that of other oceans (Venter et al, 2004;Sogin et al, 2006;Webster et al, 2010). All these contrasting results may suggest that the Red Sea is a very unique environment, different from other marine habitats.…”
Section: Influence Of Environment On Microbial Communitiescontrasting
confidence: 45%
“…Using this technology, Sogin et al have demonstrated that the previous molecular methods underestimated the true bacterial diversity by one to two orders of magnitude, and most of the observed phylogenetic diversity revealed by this new technique was represented by thousands of low-abundance populations (Sogin et al, 2006). Extremely high diversity of bacterial ribotypes in three sponge species from Australia's Great Barrier Reef and the vertical transmission of certain groups of 'spongespecific' members from sponge adults to larvae were also successfully revealed using this method (Webster et al, 2010). However, this technique has not been fully utilized to study the spatial variations of microbial communities in sponges, which may help to address the issue of stability and specificity of the microbial associates.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The advent of high-throughput, next-generation DNA sequencing platforms offers new opportunities for in-depth microbial diversity evaluation across large sample sets. Deep sequencing of microbial communities from soils, seawater and sponges has revealed diversity estimates over an order of magnitude higher than that recovered by traditional sequencing techniques (Huber et al, 2007;Roesch et al, 2007;Webster et al, 2010), including the detection of bacterial phyla not represented in firstgeneration sequencing datasets (e.g., Webster and Taylor, 2012). Similarly, the recent application of next generation sequencing to the ascidian microbiota has revealed a high diversity of symbiotic microbes and uncovered new ascidian-associated microbial lineages in the colonial host Lissoclinum patella and solitary host Styela plicata (Erwin et al, 2013), highlighting the depth of microbial biodiversity and unknown facultative and obligate symbiotic microbes awaiting discovery within ascidian hosts.…”
Section: Introductionmentioning
confidence: 99%